Strategies for Strengthening Religious Studies to Improve Mosque Jama’ah Competence - Anas, Khoirul Sidik; Mubasit, Mubasit; Mukmin, Hasan (Transpublika Publisher, 2025)
This study aims to analyze the strategy for strengthening religious studies to enhance the competence of jama’ah at Assalam Mosque, Sukarame District, Bandar Lampung. The mosque plays a vital role not only as a place of worship but also as a center for Islamic community development. In facing modern challenges, strengthening religious studies is essential to equip jama’ah with applicable religious knowledge and attitudes. A qualitative descriptive approach was employed, involving interviews, observations, and data analysis from ustadz (religious teachers), mosque administrators, and jama’ah. The findings reveal that the strengthening strategy includes the preparation of relevant and tiered study materials, interactive delivery methods, and the utilization of digital technology to broaden access and increase jama’ah participation. Furthermore, community building through social activities and psychological motivation significantly enhances jama’ah engagement. Indicators of success include improved practical religious understanding, positive behavioral changes, and active participation in religious and social activities. The study concludes that an adaptive and sustainable strategy effectively increases jama’ah competence and strengthens the mosque's role as a center for community development. These findings are expected to serve as a reference for developing religious studies in other mosques with similar characteristics.